Cardiometabolic risk profile among children with migrant parents and role of parental education: the IDEFICS/I.Family cohort - Lindblad, Anna; Samkange-Zeeb, Florence; de Henauw, Stefaan; Solea, Antonia; Veidebaum, Toomas; Lauria, Fabio; Moreno, Luis A.; Iguacel, Isabel; Molnár, Dénes; Ahrens, Wolfgang; Winkler, Volker; Lissner, Lauren; et al. (International journal of obesity, 2023)
Evidence shows that migrant children have a higher risk of developing obesity than those with native parents. We aimed to investigate the association between parental migration background and cardiometabolic health in children and adolescents in Europe.